Inhibition of ERK1/2 Restores GSK3β Activity and Protein Synthesis Levels in a Model of Tuberous Sclerosis - Rituraj Pal (Nature Portfolio, 2017)
Abstract Tuberous sclerosis (TS) is a multi-organ autosomal dominant disorder that is best characterized by neurodevelopmental deficits and the presence of benign tumors. TS pathology is caused by mutations in tuberous sclerosis complex (TSC) genes and is associated with insulin resistance, decreased glycogen synthase kinase 3β (GSK3β) activity, activation of the mammalian target of rapamycin complex 1 (mTORC1), and subsequent increase in protein synthesis. Here, we show that extracellular signal–regulated kinases (ERK1/2) respond to insulin stimulation and integrate insulin signaling to phosphorylate and thus inactivate GSK3β, resulting in increased protein synthesis that is independent of Akt/mTORC1 activity. Inhibition of ERK1/2 in Tsc2 −/− cells—a model of TS—rescues GSK3β activity and protein synthesis levels, thus highlighting ERK1/2 as a potential therapeutic target for the treatment of TS.